103k views
1 vote
I need help with this simplify 5/4+4(3/4−1/2)^2

User Ken Mc
by
4.5k points

2 Answers

0 votes


(5)/(4)+4\left((3)/(4)-(1)/(2)\right)^2 =


(3)/(4)-(1)/(2) =(3)/(4)-(2)/(4)=


\mathrm{Apply\:the\:fraction\:rule}:\quad (a)/(c)-(b)/(c)=(a-b)/(c)


=(3-2)/(4)


\mathrm{Subtract\:the\:numbers:}\:3-2=1


=(1)/(4)


=(5)/(4)+4\cdot (1)/(4)^2


\mathrm{Apply\:the\:fraction\:rule}:\quad (a)/(c)^n=(a^n)/(c^n)


=(5)/(4)+4\cdot (1)/(16)


\mathrm{Apply\:the\:fraction\:rule}:\quad \:a+(b)/(c)=(ac+b)/(c)


=(4\cdot (1)/(16)\cdot \:4+5)/(4)


\mathrm{Multiply\:the\:numbers:}\:4\cdot \:4=16


(16\cdot (1)/(16)+5)/(4) =(6)/(4) =\boxed{(3)/(2)}


\mathrm{I\:hope\:that\:I\:helped\:you\:!}

User Gabriel Milan
by
4.7k points
5 votes

Answer:

2 1/4

Explanation:

first do 4*3/4-4*1/2 because of order order of operations.

12/4-4/2=3-2=1

then do 1^2 because you do exponents before addition.

1^2=1*1=1

5/4+1=5/4+4/4=9/4

9/4=2 1/4

User Salim Nadji
by
4.8k points